Translation And Validation Of Social-Emotional Development Scale In Indonesian Language - Srinatania, Dewi; Sansuwito, Tukimin bin; Ahmed, Idris Adewale (Holistic Nursing Plus, 2025)
Background: Early-childhood social-emotional development (SED) is strongly related to lifelong well-being and academic development and mental health resilience. The absence of tools that are suitably culturally and linguistically validated for assessing SED in Indonesia nevertheless limits early opportunities for identifying developmental concerns. The objective of this study was to translate and validate the Ages and Stages Questionnaire: Social-Emotional (ASQ:SE) into Bahasa Indonesia so that it can be reliably and validly used in assessing SED for Indonesian children. Purpose: this study aimed to translate, cultural adaptation, and the validation of the ASQ:SE for Indonesian children 6 to 60 months of age, thus ensuring the soundness of any psychometric properties when applied in the local context. Methods: This cross-sectional study involved 350 parents or caregivers of children aged 6–60 months from community health centers and early childhood education programs across urban and rural areas of Java, Indonesia. The ASQ:SE was translated forward and back, reviewed by experts, and subjected to cognitive debriefing. Psychometric properties were measured by confirmatory factor analysis (CFA) for its construct validity, using Cronbach’s alpha for internal consistency, an intraclass correlation coefficient (ICC) for test-retest reliability, and known-groups validity to distinguish typically developing children from those with clinician-identified developmental delays. Results: The model fit from the CFA was acceptable (χ²/df = 2.15, CFI = 0.91; TLI = 0.89, RMSEA = 0.06). Internal consistency was very high (α = 0.86), and the test-retest reliability revealed very high stability (ICC = 0.89, 95% CI = 0.85–0.92). Known-groups validity established that the scores were significantly different (t = 5.62, p < 0.001) between typically developing children and those with developmental delays, confirming the discriminative ability of the tool. Conclusion: The Indonesian version of ASQ:SE is marked by reliability and validity that are strong enough to render it a culturally appropriate instrument for assessing the SED of Indonesian children. In clinical and educational settings, this can provide an avenue for building towards and supporting further developmental delay and thus child development.